Synthesis of Benzopyranopyrazoles - Kumbhare, R.M.; Chinchkhede, P.W.; Ingle, V.N. (Asian Journal of Chemistry, 2010)
3-Aryl-4-arylidine-5-(o-hydroxyphenyl)-pyrazoles (2) and 2,7- diaryl-4H-1-(3,4-c)-benzopyranopyrazoles (3) are obtained by the condensation of 2'-hydroxy-2-aroyl-3-aryl-acrylophenones and hydrazine hydrate and oxidative cyclization of (2) with selenium dioxide respectively. Their structures have been supported on the basis of elemental analysis and spectral data.